Knowledge of kinnow growers with respect to the recommended practices including post harvest technology - Singh, Kuldeep; Dangi, K.L.; Singh, Narpat (Annals of Agricultural Research, 2017)
The study was conducted in Sri Ganganagar and Sri Karanpur panchayat samities of Sri Ganganagar district. The majority of respondents (63.30 per cent) were from medium knowledge category, while 17.30 per cent placed under high category. The proportion of respondents the low knowledge was 19.33 per cent. The extent of knowledge of big farmers were found to be substantially higher than the small farmers about recommended practices of kinnow cultivation. Results indicated that there was significant difference in knowledge between small and big farmers regarding recommended practices of kinnow cultivation in the study area.